“Apparently, their mother gave birth to them on Monday…” (on the earliest note to the oldest full manuscript of the Arabic Bible) - Serge Frantsouzoff (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2023)
In the article the earliest note to the oldest complete copy of the Bible translated into Arabic, kept now in the Institute of Oriental Manuscripts of the RAS under shelf-mark D 226, t. 1–3, is edited with Russian translation and commentary. It contains the precise datings of two events: the entry of the Ottoman Sultan Selim I on the 27th of Radjab of AH 922 (the 26th of August of AD 1516) and the defeat of the rebel army of the Mamluk Djan-Birdi al-Ghazali by Ottoman troops on the 27th of Safar of AH 927 (the 5th of February of AD 1521). Both of them occurred on Tuesday which in the Middle East was considered as an unlucky day of the week by the Christians as well as by the Muslims. It is interesting to remark that the note is located just before the beginning of the Book of Genesis that tells about the days of Creation, from which the days of the week derive. Among the four political figures attested in the note the author succeeded in identifying three: besides two mentioned above this was Farhat-Bey who in spring of AD 1521 was appointed the governor of Tripoli where the customers of the oldest Arabic Bible probably lived. The manuscript was copied, while the events attested in the note remained relevant, i.e. shortly before or after them, just around AD 1521.